Fly ash porous material using geopolymerization process for high temperature exposure - Mohd Mustafa Al Bakri, Abdullah; Liyana, Jamaludin; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr.; Mohamed, Bnhussain; Che Mohd Ruzaidi, Ghazali, Prof. Madya; Mohd Izzat, Ahmad (MDPI AG (Basel, Switzerland), 2013)
Link to publisher's homepage at http://www.mdpi.com/